Consumer learning behavior in adoption Tani Hub e-commerce - Maulavida Qholbyah Rahmah (Universitas Airlangga, 2021)
As e-commerce develops in Indonesia, sales of fresh fruit and vegetable products move from physical stores to virtual markets through technological innovation. The adoption of e-commerce is marked by changes in purchasing behavior of fresh fruits and vegetables that originally relied on the senses, now mediated by a screen measuring at least 7 inches. Interaction between seller and buyer, or buyer with buyer also mediated. This condition does not require consumers to be able to see, hold and smell the product they want directly. When compared with conventional methods, the purchase of fresh vegetables and fruit through e-commerce has risks, namely uncertainty such as the physical quality of the product, taste or freshness. Consumers need knowledge and experience to reduce this uncertainty, where this knowledge and experience is obtained through a consumer learning process. This study describes the forms of consumer learning behavior starting from the beginning to get acquainted with adopting e-commerce. The research method used is qualitative with descriptive research type, and the method of data collection in the form of in-depth interviews with informants who are adopters of the Surabaya branch of the E-Commerce Tani Hub. This informant consists of a group of friends who have the same values, namely implementing a lifestyle and eating healthy food. The results of this study are in the form of learning behaviors shown by Tani Hub consumers through the process of information exchange with information sources that they consider credible, namely friendship circles and also primary information from the Tani Hub’ company itself.